SECOND IN ORDER PARAMETERIZED PRIVATE DERIVATIVE DIFFERENTIAL EQUATIONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In this article to the parameter depends private derivative differential equations concept formed. This equations with expressible practical issues and their mathematician models given. Harvest done to the parameter depends private derivative differential the equation parameterized simple differential equation to solve to bring method shown.